2013
DOI: 10.1536/ihj.54.48
|View full text |Cite
|
Sign up to set email alerts
|

Successful Conversion From Thiazide to Tolvaptan in a Patient With Stage D Heart Failure and Chronic Kidney Disease Before Heart Transplantation

Abstract: SummaryChronic kidney disease (CKD) is often complicated with advanced heart failure because of not only renal congestion and decreased renal perfusion but also prolonged use of diuretics at higher doses, which sometimes results in hyponatremia. Preoperative CKD is known to be associated with poor prognosis after heart transplantation (HTx). We experienced a stage D heart failure patient with CKD and hyponatremia who was switched from trichlormethiazide to tolvaptan. His hyponatremia was normalized, and his re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] In contrast, we sometimes experience TLV-non-responders in our daily clinical practice. 11) We previously proposed a novel predictor of responsiveness to TLV, ie, the baseline urine aquaporin-2 (U-AQP2) level relative to the plasma AVP (P-AVP) level, which may indicate a preserved vasopressin type 2 receptor (V2R)-related signaling pathway in the principal cells of the renal collecting duct.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In contrast, we sometimes experience TLV-non-responders in our daily clinical practice. 11) We previously proposed a novel predictor of responsiveness to TLV, ie, the baseline urine aquaporin-2 (U-AQP2) level relative to the plasma AVP (P-AVP) level, which may indicate a preserved vasopressin type 2 receptor (V2R)-related signaling pathway in the principal cells of the renal collecting duct.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] We also reported the effi cacy and safety of TLV in (1) amelioration of congestion even in stage D HF patients and (2) improvement of renal function by converting ongoing diuretics to TLV. 8,9) With respect to serum sodium concentration (S-Na), various studies in Europe and the United States have demonstrated the effi cacy of TLV to improve hyponatremia with little chance of hypernatremia, ie, S-Na > 145 mEq/L (eg, 1.7% of hypernatremia in the EVEREST study and 0% in the QUEST study). 2,6,[10][11][12] In Japan, we can administer TLV to HF patients to treat their congestion regardless of baseline S-Na as long as hypernatremia or rapid increases in S-Na do not develop.…”
mentioning
confidence: 99%
“…Therefore, longer administration of TLV under reduced doses of conventional diuretics may be necessary for signifi cant reversal in renal function as well as normalization of serum sodium concentration, as was observed in our previous case. 10) We acknowledge that our study has several limitations. First, it was conducted retrospectively in a single center, and consequently included a limited number of patients and may have patient selection bias.…”
Section: Discussionmentioning
confidence: 95%
“…8) We also reported cases in which TLV could improve hyponatremia and/or renal function without compromise of hemodynamics in patients with stage D HF. 9,10) However, TLV is sometimes ineffective in a certain number of patients with HF, but the definition of a good response to TLV has not yet been established. 3,11) We have used the defi nition of "responders" as patients with any increase in urine volume (UV) at day 1 when we started TLV administration, and proposed novel criteria consisting of 2 parameters on urine osmolality (U-OSM) that could predict responsiveness to TLV in decompensated HF patients.…”
mentioning
confidence: 99%